Quantity discount for integrated supply chain model with back order and controllable deterioration rate - Mishra Poonam; Talati Isha (Yugoslav Journal of Operations Research, 2018)
Due to uncertainty in economy, business players examine different ways to ensure the survival and growth in the competitive atmosphere. In this scenario, the use of effective promotional tool and co-ordination among players enhance supply chain profit. The proposed model deals with the effect of quantity discount on an integrated inventory system for constantly deteriorating items with fix life time. We use advertisement and quantity discount to accelerate stock dependent demand and further, the offered preservation technology for controlling deterioration rate. The model is validated numerically, and the sensitivity analysis for critical supply chain parameters is carried out. The results can be used in the decision making process of the supply chains associated with the supply of cosmetic, tinned food, drugs, and other FMCGs.